(untitled) (Bangladesh Journal of Medical Science, 2015)
Benign prostatic hyperplasia often produces chronic and progressive lower urinary tract symptoms or complications such as bladder stone, leading to retention of urine and to seek medical attention. Becharetal1 stated giant urinary bladder stone weighing 100 grams or more are uncommon. In our case 162 grams of bladder stone with few another stones about 10-15 grams in the left lower end of ureter were removed. Available treatment options for vesical calculus include open surgical removal, extracorporeal fragmentation and endoscopic crushing. Recently endo-surgical mechanical cystolithotripsy followed by percutaneous extraction has been in clinical practice for small and moderate sized calculus. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21573 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.98-99